Żydzi w Szadku – rys historyczny - Stulczewski, Jarosław (Biuletyn Szadkowski, 2010)
The earliest mention of Jews in Szadek dates from the early 16th century, but it was in the second half of the 18th century, that this nationality group became more numerous and started gaining prominence in the socio-economic life of this town. In 1913, every third resident of Szadek (2.8 thousand inhabitants at that time) was Jewish. The majority of trading was carried out by Jews – there were 34 shops run by Jews, and only 7 were kept by Catholics. During the Second World War most of the Jews from Szadek were put to death in a concentration camp in Chełm on the River Ner; the few who survived the occupation soon emigrated. Almost no material trace has remained of this nationality group, which had for centuries been an important component of local community, in terms of both socio-economic and cultural development. The only material evidence, being a memorial to the Jewish community in Szadek, is a Jewish cemetery, recently restored after post-war devastation.